Fieldwork with Bowerbirds - Phillips, Perdita (Antennae, 2012)
Fieldwork with Bowerbirds. From 2007 to 2008 Perdita Phillips visited the Broome Bird Observatory (BBO) in northern Western Australia working on the art and science project Green, Grey or Dull Silver: art and the behavioural ecology of the Great Bowerbird, Chlamydera Nuchalis. It involved observing and interacting with the common and largely sedentary Great Bowerbirds that live in the surrounding pindan savannah. Text by Perdita Phillips